Cost of nursing staffing adequacy in a neonatal unit - Fugulin, Fernanda Maria Togeiro; Lima, Antonio Fernandes Costa; Castilho, Valéria; Bochembuzio, Luciana; Costa, Janaína Anchieta; Castro, Liliana; Silva, Natália Célia Lima; Gaidzinski, Raquel Rapone (Revista da Escola de Enfermagem da USP, 2011)
The objectives of this descriptive, quantitative study were: to identify the mean nursing care time provided and required by newborns (NB) hospitalized at the Neonatal Unit of the University of São Paulo University Hospital; to calculate the cost of the mean nursing care time provided and required, by NB; to assess the cost of the nursing staffing adequacy required to assist the NB. The mean nursing care times, provided by the nursing staff and required by NBs, were calculated using equations available in the literature and by applying the Nursing Activities Score. The costs of the mean nursing care times and to make nursing staffing adequate were calculated based on the hourly cost of nurses and nursing technicians. The financial impact of nursing staffing adequacy accounted for a 30% increase over the cost of the current situation.